Double Lap Shear Testing of Coating Modified Ice Adhesion to Liquid Oxygen Feed Line Bracket, Space Shuttle External Tank - Ferrick, M. G.; Mulherin, N. D.; Haehnel, R. B.; Coutermarch, B. A.; Durell, G. D.; Tantillo, T. J.; St. Clair, T. L.; Weiser, E. S.; Cano, R. J.; Smith, T. M.; Martinez, E. C. (2006)
The brackets that secure the liquid oxygen feed line to the external tank are known locations of frost and ice growth during the period following fuel loading. This experiment quantified the reduced adhesion when ice phobic coatings were applied to test coupons simulating the bracket surface. Double lap shear testing of coated and uncoated coupons provided robust test specimens and consistent load response patterns with exceptional resolution. For these tests ice was grown as strong and consistently as possible, subjected to temperature decreases comparable to those of the prototype bracket, and tested at a controlled temperature of 112 C. The tests evolved in three phases, with uncoated controls included in each group of tested samples. The first phase of testing evaluated a wide range of coatings, and showed that Rain-X mixed with MP-55 powdered Teflon (RXM) was an outstanding coating to reduce ice adhesion to Koropon coated aluminum. However, significant amounts of coating were retained on the ice surface following each test, indicating failure in the coating and potential loss of effectiveness with repeated ice formation and release. Phase 2 evaluated potential modifications to RXM that might maintain effectiveness and enhance durability. However, the modified RXM mixtures did not improve the ice adhesion performance or coating durability. The original document contains color images.